Measurement of the shape of the B0S → D[ast]−Sμ+νμ differential decay rate - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2020)
The shape of the B0s→D∗−sμ+νμ differential decay rate is obtained as a function of the hadron recoil parameter using proton-proton collision data at a centre-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 1.7 fb−1 collected by the LHCb detector. The B0s→D∗−sμ+νμ decay is reconstructed through the decays D∗−s→D−sγ and D−s→K−K+π−. The differential decay rate is fitted with the Caprini-Lellouch-Neubert (CLN) and Boyd-Grinstein-Lebed (BGL) parametrisations of the form factors, and the relevant quantities for both are extracted.
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, G. Frau, D. Gerick, J. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, A. Piucci, S. Stemmle, D.A. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und 977 weitere]
Im Titel ist [ast] als Tropfensternchen (englisch: teardrop-spoked asterisk) dargestellt
Im Titel sind "0", "[ast]", "-", "+" hochgestellt, "S" jeweils tiefgestellt
Gesehen am 22.02.2021